Additional Diagnostic Value of Unenhanced Computed Tomography plus Diffusion-Weighted Imaging Combined with Routine Magnetic Resonance Imaging Findings of Early-Stage Gliblastoma. (18th February 2020) - Wang, Hexiang; Liu, Zhenyou; Zhang, Yong; Hou, Feng; Fu, Weiwei; Lin, Jizheng; Liu, Yingchao; Liu, Xuejun
Abstract : Purpose . This study was performed to determine whether diffusion-weighted imaging (DWI) plus unenhanced computed tomography (CT) of the brain increases the diagnostic value of routine magnetic resonance (MR) imaging findings of early-stage glioblastoma. Methods . Postcontrast MR images of eight unenhanced lesions that had been pathologically diagnosed as glioblastoma were retrospectively examined. The location, margin, signal intensity, and attenuation on MR imaging and CT were assessed. Results . On MR imaging, all lesions were ill-defined, small, and isointense to hypointense on T1-weighted images and hyperintense on T2-weighted images. Four patients had perilesional edema. In seven patients, DWI showed an inhomogeneous hyperintense lesion ( n = 1) or isointense lesion with a hyperintense region ( n = 6). On unenhanced CT, all masses presented as a hypoattenuated lesion with a hyperattenuated region ( n = 7) or isoattenuated region ( n = 1). The hyperattenuated region ( n = 6) or isoattenuated region ( n = 1) on CT appeared on DWI as an inhomogeneous hyperintense lesion ( n = 1), isointense lesion with a hyperintense region ( n = 3), or ring-like peritumoral hyperintensity ( n = 3). Conclusions . MR imaging was the most sensitive imaging method for depicting early-stage glioblastoma. The CT finding of a hyperattenuated or isoattenuated region combined with the DWI finding of the same region containing an inhomogeneous hyperintense lesion or isointense lesion with a hyperintense region may be a specific diagnostic sign for early-stage glioblastoma. DWI plus unenhanced CT added diagnostic value to the routine MR imaging findings of early-stage glioblastoma.